Medusa’s Gaze and Vampire’s Bite: The Science of Monsters by Matt Kaplan - Bullard, Thomas E. (Journal of Scientific Exploration, 2013)
The Dark Ages lie deep in the past, the isolated folk community has grown almost as rare as the unicorn. Nevertheless it is amid this modern age of technology and enlightenment that we live in the golden age of monsters. They no longer crouch under the bed at night but leap out from the big screen in 3-D. Turn on the TV, pick up a popular novel, and you risk attack by vampires, zombies, dinosaurs, or aliens-while abundant videogames offer an opportunity to fight back. Monsters have stayed with us throughout human history but their persistent and insistent intrusion in modern times poses a phenomenon in need of scholarly attention, and such attention is now very much at hand. A subject that was once beneath academic dignity as mere fashion in lowbrow entertainment or superstitious survivals from the childhood of the species has risen to prominence across multiple disciplines. The grounds of that interest underlie not so much the monsters themselves as a realization that if monsters saturate modern culture, that fact tells us something about ourselves; and even if we no longer need to hunt the primeval forest for our quarry or venture beyond where the map leaves off, understanding the monstrous is no less important, and perhaps all the greater because the source lurks so close to home. Why do we love our monsters so? Why do we even have monsters, of all things? Don't we know better? The issues inspired by the universal presence of big, ugly, dangerous, and disturbing creatures breaking into the order of the everyday world have given rise to an impressive scholarly literature. Anthropologists inventory the prolific array of monsters recognized by peoples around the world, and consider the social functions these creatures serve. Folklorists and psychologists have pondered the monster as a personification of otherness, an expression of deep-seated fears, or a response to the uncertainties of modern life. Literary scholars long preoccupied with the role of the hero are now giving his adversary its due, while books, articles, and conferences devoted to cinematic treatments of vampires and TV series like Buffy the Vampire Slayer have mined the rich representation of these creatures as romantic anti-heroes and outsiders at once alluring and terrifying. Zombies derive their popularity as versatile metaphors for a consumer society wherein everyone performs only mindless routines, while all too many of us join the ranks of the cell-phone variety to stumble around in semi-conscious oblivion. For scholars of religion the monster of ancient as well as modern texts exemplifies the forces of chaos ever biding, always threatening the divine order. Postmodernists look ahead to see our monsters portrayed more and more as human inventions. For example, the monster movies of the patriotic 1950s cast scientists and the military as heroes saving the world from aliens and creatures from the deep, while the countercultural 1960s began a turnaround that transformed the former heroes into the villains creating robots, hybrids, and viruses that threatened the world.